2019
DOI: 10.1111/rsp3.12223
|View full text |Cite
|
Sign up to set email alerts
|

Citizens' perception of the Cohesion Policy and support for the European Union

Abstract: Using a novel database, this study assesses the impact of the perception of the personal benefits of the EU Cohesion Policy on support for the European project. The results show that the gap in support between people who claim to have benefited from the Cohesion Policy and those who feel they have not vanished once differences in individual traits and reverse causality are taken into account. This means that, despite the significant positive effect that the intensity of the Cohesion Policy in the region exerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Empirical research on the effectiveness of the cohesion policy in the lagging regions of Slovakia has also shown that its impact has been marginal and only short term (Némethová, Širaňová, & Šipikal, 2018). The lack of awareness of the EU assistance provided to the region is also a frequently mentioned factor in the literature in this field (López‐Bazo & Royuela, 2019). Last important finding in this section is that it may sense to distinguish between the various types of cohesion aid, as they can have different effects on the electoral behaviour of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research on the effectiveness of the cohesion policy in the lagging regions of Slovakia has also shown that its impact has been marginal and only short term (Némethová, Širaňová, & Šipikal, 2018). The lack of awareness of the EU assistance provided to the region is also a frequently mentioned factor in the literature in this field (López‐Bazo & Royuela, 2019). Last important finding in this section is that it may sense to distinguish between the various types of cohesion aid, as they can have different effects on the electoral behaviour of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this issue received great attention, witnessed by the funding of two Horizon 2020 projects 6 (Capello and Perucca, 2018;Aiello et al, 2019), aimed at understanding the relationship between Cohesion Policy implementation and citizens' identification with Europe. This stream of research generally pointed out a positive association between EU funding and European identity, subject however to the mediation of several factors, namely the level of awareness and satisfaction with the actions undertaken (Capello and Perucca, 2019), the implementation of effective strategies of information, communication and the involvement of the local population (López-Bazo & Royuela, 2019;Smętkowski & Dąbrowski, 2019). Coherently with this evidence, in the context of this paper Cohesion Policy is expected to decrease the identity gap in favour of national over European identity.…”
Section: The Determinants Of the Identity Imbalancementioning
confidence: 59%
“…They unveil that EU transfers increase support for European integration. Nevertheless, López-Bazo and Royuela (2019) found that the intensity of the Cohesion Policy did not stimulate support for the EU.…”
Section: Introductionmentioning
confidence: 94%